Digital Heritage. Progress in Cultural Heritage : Documentation, Preservation, and Protection : 6th International Conference, EuroMed 2016, Nicosia, Cyprus, October 31 – November 5, 2016, Proceedings, Part II /: Documentation, Preservation, and Protection : 6th International Conference, EuroMed 2016, Nicosia, Cyprus, October 31 – November 5, 2016, Proceedings, Part II. (2016) - Unknown
No abstract available